Observations on Growth and Productions of Indian Major Carps through composite Fish Culture under different Management practices - Totawar DV; Tamlurkar HL (International Journal of Life Sciences, 2017)
Three fish culture ponds (P1, P2 and P3) in Nanded district of M.S. under different management practices were selected for study over a period of two years. In the pond P1, culture of Indian major carps was carried without any fertilization or supplementary feeding while in pond P2 fertilization was done without any supplementary feeding. In pond P3, culture was carried out both with fertilization and supplementary feeding. The physic-chemical parameters of water, primary production, growth and fish production varied significantly among the three ponds which could be attributed to the different levels of inputs used in the fish culture. The results of present study indicate that high stocking density, supplementary feeding, regular liming, intermittent fertilization and manuring contributed to considerably high fish production. The average production of fish was significantly higher (P<0.01) in the pond P3 in comparison to ponds P2 and P1 The length-weight relationship of the cultures species in the experimental ponds was calculated by linear regression equation and exponential equation.